2011
DOI: 10.1080/15538362.2011.554076
|View full text |Cite
|
Sign up to set email alerts
|

Potential Nitrogen Contributions from Legumes in Pacific Northwest Apple Orchards

Abstract: As costs for nitrogenous fertilizers become increasingly expensive, organic and conventional apple producers recognize the potential to integrate leguminous plants in the orchard agro-ecosystem to contribute to N nutrition. We evaluated alfalfa as a drive row cover and white clover as an under tree living mulch. Both impacted nitrogen dynamics and tree performance. Alfalfa did not adversely affect tree growth and yield while potentially contributing to tree N nutrition. The white clover living mulch, clearly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
8
1
Order By: Relevance
“…With only an estimated 7% of the nitrogen in the added alfalfa residue mineralized and measured in the soil over 21 d, it is difficult to assess the effects of the treatments on long term mineralization. This is considerably lower than a previous estimate of 43% using the same method on another site with white clover (Mullinix and Granatstein, 2011). The clover may have been easier to degrade than the alfalfa because of clover having more leaves and less resistant stems.…”
Section: Resultscontrasting
confidence: 61%
See 2 more Smart Citations
“…With only an estimated 7% of the nitrogen in the added alfalfa residue mineralized and measured in the soil over 21 d, it is difficult to assess the effects of the treatments on long term mineralization. This is considerably lower than a previous estimate of 43% using the same method on another site with white clover (Mullinix and Granatstein, 2011). The clover may have been easier to degrade than the alfalfa because of clover having more leaves and less resistant stems.…”
Section: Resultscontrasting
confidence: 61%
“…In addition, they typically result in far more light reaching the orchard floor, which creates the opportunity to grow plants on the orchard floor for specific purposes, such as flowering species to support beneficial insects or legumes for nitrogen fixation (Granatstein and Sanchez, 2009). This could occur in the tree row, as a ''living mulch'' or in the drive alley, where the legume biomass could be mowed in place, mowed, and blown on to the tree row, or incorporated into the soil (Mullinix and Granatstein, 2011). In the Pacific Northwest United States, nitrogen is the macronutrient most often needed on a yearly basis to sustain fruit production (Neilsen and Neilsen, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Black et al, (2010) showed that root growth of tart cherry in orchards managed with a grass alleyway was primarily constrained to the area below the herbicide strip, confirming the need for weed control in orchards managed with grass alleyways. Locating legumes in the alleyway versus the tree-row, as in this study, may be critical to reducing competition in the alleyway, hence optimizing the benefits of orchard-grown legumes and reducing tree susceptibility to weed pressure (Granatstein and Sánchez, 2009;Mullinix and Granatstein, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Stasiak and Rom (1991) indicated that competition effects may be short lived in establishing peach orchards, however. In addition, locating the legumes in the alleyway versus the tree-row may be critical to reducing competition and optimizing benefits (Granatstein and Sánchez, 2009;Mullinix and Granatstein, 2011).…”
Section: Introductionmentioning
confidence: 99%